Immunization Financing Assessment : Nigeria - Alkenbrack, Sarah (World Bank, Washington, DC, 2021)
Nigeria has the highest population of unimmunized children in the world and is one of few countries with less than half the population covered with essential health services. Low coverage of services poses a threat to the health and well-being of Nigerian children, but this threat becomes even more pronounced against a backdrop of the ‘health financing transition’, including the transition from support from the Gavi Alliance, the main source of financing for the country’s immunization program. The Nigeria Immunization Financing Assessment shows how the factors at multiple levels of government and the health system interact to affect four dimensions of health and immunization financing: adequacy; sustainability; efficiency; and predictability. The findings informed the design of the Nigeria Strategy for Immunization and PHC System Strengthening (NSIPSS), which will be used to guide the country as it transitions from Gavi support. This paper emphasizes the need to implement the NSIPSS in close coordination with the current reforms underway in the health sector. Currently, the government of Nigeria is piloting reforms at federal, state, and local levels to fast track implementation of the National Health Act, which aims to bring additional and ‘smarter’ domestic resources for health to the facility level. Also needed are systematic linking of health plans to budgets, more efficient allocation of resources, coordinated advocacy, exploration of demand-side barriers to service delivery, capacity building, and strengthened accountability mechanisms that ensure investments in health lead to improved health outcomes. A transition planning process that is grounded, backed by evidence, monitored and adapted regularly, and backed by the highest level of the government of Nigeria will be critical for changing the trajectory for the children of Nigeria.